Serology, molecular detection and risk factors of Ehrlichia canis infection in dogs in Costa Rica - Dolz, Gaby (2016)
tA cross-sectional study combining different serological and molecular techniques for the detection ofEhrlichia species in dogs and their ticks was carried out with data from all regions of Costa Rica. A sero-prevalence of 32.1% (131/408), and infection with E. canis of 3.2% (13/407) was found, whereas 6.9%(9/130) of ticks attached to the dogs were PCR positive to E. canis. Higher prevalences were found out-side the Greater Metropolitan Area (GMA). Risk factors associated with E. canis seropositivity were age,between 2 and 7 years (RR: 1.6, 95% CI: 1.2–2.2) and 8–15 years (RR: 1.8, 95% CI: 1.2–3.0), number ofdogs/total of households [Dogs per Household Ratio (DHR) ≥3.1 (RR: 2.0; 95% CI: 1.4–3.0)], number ofdogs infested with at least one tick/total of dogs sampled [Tick Infestation Prevalence (TIP) ≥ 31% (RR: 2.1;95% CI:1.3–3.3)] and living outside the GMA (RR: 1.7; 95% CI: 1.2–2.4) and being a mixed-breed dog (RR:1.5; 95% CI: 1.1–2.1). Risk factors for E. canis PCR positive dogs were a depressive attitude (OR: 11.2; 95%CI: 1.1–115.9), fever (OR:4.8; 95% CI:1.2–19.3), DHR ≥3.1 (OR: 5.7; 95% CI:1.7–19.2)], number of ticks/totalof dogs sampled [Tick Distribution Ratio (TDR) ≥2.1 (OR: 6.5; 95% CI: 1.3–31.8)], and TIP ≥40% (OR: 5.7;95% CI: 1.7–19.2). This paper describes E. canis seroprevalence, PCR prevalence and tick analysis in dogsfrom Costa Rica, with associated clinical signs and owner perceptions. In summary, most of the E. canisinfections in dogs in our country seemed to pass unnoticed by owners. Since most of the seropositivedogs (97.7%, 131/134) were negative for E. canis DNA in their blood, it is important to determine in futurestudies if these dogs recovered from the E. canis infection without any medication, or are persistentlyinfected, and will develop chronic disease.